Examining the mediating-moderating role of psychological contract breach and abusive supervision on employee well-being in banking sector - Saba Gulzar; Nadia Ayub; Zuhair Abbas (Cogent Business & Management, 2021)
Previous research rarely examined the antecedents of employee well-being with the interactive effect of abusive supervision and mediating impact of psychological contract breach especially in the developing country context. Drawing upon the social exchange theory, this study attempts to bridge a research gap by investigating work engagement, work-life balance, and turnover intention with employee well-being directly and through the moderating and mediation effects of abusive supervision and psychological contract breach. To validate these relationships, 208 employees who are working in banks of Pakistan were investigated, through a survey-based questionnaire. The Smart PLS 3.0 was employed to measure the association and test the hypotheses in which structural equation modelling played a role in checking the relationships among variables. The results demonstrate that work engagement, work-life balance, and turnover intention directly affect employee well-being. This study also found that psychological contract breach has a partial mediation effect between work engagement, work-life balance, turnover intention, and abusive supervision with employee well-being. Additionally, this study shows that abusive supervision has a moderating impact between psychological contract breach and employee well-being. This study contributes to the literature and body of knowledge in human resource management and organizational behaviour. This study helps to better understanding employee well-being at micro-level in a service sector especially in developing country context (Pakistan). Finally, this study helps managers to express their feedback, suggestions, and interaction with employees.
Keywords: 650; Psychological contract; psychological contract breach; work engagement; work life balance; turnover intention; abusive supervision; employee wellbeing